Media Pembelajaran Video Animasi Stop Motion pada Materi Sistem Sirkulasi Manusia untuk Meningkatkan Keterampilan Berpikir Kritis Siswa - Muzammil, Imal; Kurniasih, Surti; Jaenudin, Dadang (PSEJ (Pancasakti Science Education Journal), 2023)
study aims to produce products in the form of Stop motion animation learning media and obtain information on students' critical thinking skills on circulation system materials. This research is a development research or Research and Development (R&D) with a research design carried out referring to the 4-D development model by Thiagarajan et al., (1974). The 4-D development model consists of define, design, develop, and dessiminate stages. Of the four steps, only three steps were carried out in accordance with the limitations of the study. Data collection is carried out in a quantitative descriptive manner. The results of this study showed that the learning media got an average score of 3.66 which means it is very good based on expert assessment, the CVR score got a score of 3.90 and CVI got a score of 0.94. The results of the student's critical thinking skills test before using stop motion animation media scored 56.53 and after using the media scored 82.53.